PENGARUH PEMAHAMAN PAJAK DAN BIAYA TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KEMUDAHAN SISTEM E-FILING SEBAGAI VARIABEL MODERASI - Ernawan Septia Putri Ussholehah,; Baldric Siregar,; Frasto Biyanto,; Miswanto, Miswanto (Juremi: Jurnal Riset Ekonomi, 2025)
This study aims to determine the effect of understanding taxation, compliance costs on taxpayer compliance with the ease of the e-filing system as a moderating variable. The method used is a quantitative approach and uses individual taxpayers as the unit of analysis. The sample was taken using a purposive sampling technique and the criteria were taxpayers who already had an NPWP and had used the e-filing system as a tax return reporting process. The sample size was 104 respondents. Data collection was carried out by distributing questionnaires through social media. The data was processed using SPSS version 22.0 and using multiple linear regression analysis techniques. The results showed that tax understanding has a significant positive effect on taxpayer compliance, compliance costs have a significant positive effect on taxpayer compliance, the ease of the e-filing system moderates tax understanding has a significant positive effect on taxpayer compliance, the ease of the e-filing system moderates compliance costs has a negative and insignificant effect on taxpayer compliance.